2008
DOI: 10.1111/j.1751-7915.2008.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole and 7‐hydroxyindole diminish Pseudomonas aeruginosa virulence

Abstract: SummaryIndole is an extracellular biofilm signal for Escherichia coli, and many bacterial oxygenases readily convert indole to various oxidized compounds including 7‐hydroxyindole (7HI). Here we investigate the impact of indole and 7HI on Pseudomonas aeruginosa PAO1 virulence and quorum sensing (QS)‐regulated phenotypes; this strain does not synthesize these compounds but degrades them rapidly. Indole and 7HI both altered extensively gene expression in a manner opposite that of acylhomoserine lactones; the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
253
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(271 citation statements)
references
References 82 publications
(179 reference statements)
12
253
1
5
Order By: Relevance
“…The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…strain [25] use indole as a growth substrate. While, Pseudomonas indoloxidans, P. aeruginosa [7], A. tumefaciens [10], and Burkholderia unamae strain CK43-B [26] can degrade indole without utilizing it as the sole carbon source. D. indolicum is the only anaerobic isolate identified to date that can utilize indole as a carbon and electron donor [27].…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 85 Gram-positive and Gram-negative bacterial species that yield indole as the product of tryptophan metabolism [1]. Biochemical and molecular studies have shown that indole plays various roles in bacterial systems, for example, as an extracellular signal [1,3], for multicopy plasmid maintenance [4], cell division, biofilm formation [5], and acid and drug resistance [5][6][7][8]. In addition, indole also controls the virulence of several pathogenic bacteria [7] and it has multifaceted properties and applications in prokaryotic systems [9][10][11] as well as eukaryotic systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…An example of this statement is the production of the siderophore pyoverdine by Pseudomonas fluorescens (39), which is related to virulence and pathogenicity of the microbe at the clinical level (45)(46)(47). Nagata and co-workers (39) found that pyoverdine production enhanced iron nutrition of tomato plants (Strategy I plants, which cannot produce pyoverdine).…”
Section: Plant Growth and Biocontrol Of Pathogensmentioning
confidence: 99%